A Post Mortem Study to Detect Any Variation in the Volume of the Human Pituitary Gland in Relation to Age (Bangladesh Journal of Anatomy, 2014)
Context: The pituitary gland is called “the master gland”, as it controls the secretion of other important endocrine glands of the body. Various clinical problems may occur due to hypo-functional and hyperfunctional state of the hormones of the pituitary gland. Therefore, the study is important to determine the normal variation of the volume of the gland with advancing age which will help to define its function at different stages of life.Materials & Methods: A cross-sectional analytical type of study was carried out in the Department of Anatomy, Dhaka Medical College, on 60 human pituitary glands (40 male and 20 female)- collected from unclaimed dead bodies. The samples were divided into four groups. i.e. Group A (20-29 years), Group-B (30-39 years), Group-C (40-49 years) and Group-D (50-59 years). The three dimensions of pituitary gland (height, width and length), was recorded by using a digital slide calipers in mm and the volume of each pituitary gland was measured by applying the ellipsoid formula.Results: The mean ± SD of volume of whole pituitary gland in different age group was 196.49 ± 43.82, 176.70 ± 53.58, 146.38 ± 39.10 and 107.13 ± 11.90 mm³ in group A, B, C and D respectively. The mean± SD of volume of the whole pituitary gland was186.11 ± 56.98, 160.47 ± 57.65,129.38 ± 28.06 and 107.13 ± 11.896 mm³ in group A, B, C and D in male respectively. In female the mean ± SD of volume was found 206.88 ± 24.29, 211.18 ± 15.77 and 197 ± 7.55 mm³ in group A, B, and C respectively.Conclusion: The volume of the pituitary gland showed gradual decreasing values with advancing age. The mean ± SD of volume of male gland in this study was statistically lower than that of female glands.Bangladesh J. Anat. 2014; 12(2) : 44-50